Role of LECT2 in exacerbating atopic dermatitis: insight from in vivo and in vitro models via NF-κB signaling pathway - Liu, Zhifang; Jiang, Xinyu; Zhao, Keyu; Ruan, Hongyu; Ma, Yizhao; Ma, Yuhan; Zhou, Qiongyan; Zhang, Jing; Sun, Xiaoyan; Ma, Wenxue; Xu, Suling (Frontiers in Immunology, 2024)
Leukocyte cell-derived chemotaxin 2 (LECT2) is linked to various immune diseases. Previously, we reported that serum LECT2 levels correlate with disease severity in atopic dermatitis (AD) patients. To investigate the role of LECT2 in AD and elucidate its potential mechanisms, we used LECT2 to treat an AD mouse model induced by 1-Chloro-2,4-dinitrobenzene (DNCB) in LECT2 knockout (KO) and wild-type (WT) mice, and an AD cell model using TNF-α/IFN-γ-induced HaCaT cells. Inflammatory factors and barrier proteins were analyzed by histology, immunohistochemistry, RT-qPCR, ELISA, and Western Blot. Activation of the NF-κB signaling pathway was evaluated by Western Blot and immunofluorescence. In the AD mouse model, LECT2 treatment increased epidermal and dermal thickness, mast cell infiltration, and downregulated barrier proteins. Inflammatory factors were increased in skin lesions and serum. In the AD cell model, LECT2 decreased barrier protein levels and increased inflammatory factor levels, enhancing NF-κB P65 nuclear translocation. These results indicate that LECT2 exacerbates AD-like responses by dysregulating the NF-κB signaling pathway, highlighting its potential as a therapeutic target for AD management.